The Influence of Fundamental Factors and Digitalization on Firm Value Mediated by Corporate Social Responsibility in the Kompas 100 Index Companies in Indonesia - Yappy, Ruddy; Leon, Farah Margaretha; Lestari, Henny Setyo; Muchtar, Susy (Dinasti Publisher, 2026)
Rapid economic growth amid environmental threats demands global governance capable of balancing green development with ecological sustainability, while also encouraging corporate contributions through Corporate Social Responsibility (CSR) to enhance Firm Value. The phenomenon of increasing Initial Public Offering (IPO) activities in Indonesia, particularly in the renewable energy sector and electric vehicle raw materials, demonstrates the strategic role of the capital market in supporting national economic growth. This study aims to examine the influence of Good Corporate Governance (GCG), capital structure, profitability, dividend policy, Digitalization, and gross domestic product on firm value with CSR as a mediating variable. The method used is a quantitative approach with secondary data from 100 companies listed in the Kompas 100 Index for the period 2020–2024 through purposive sampling. The research results show that CSR has a strategic role as a mediating mechanism in the relationship between internal company factors and Firm Value, although the direction of its influence is not always consistent with the theoretical hypothesis. These findings contribute to the literature on corporate governance, financial strategy, and Digitalization, and offer practical implications for management in designing CSR policies that can sustainably enhance Firm Value.